PRACTICE OF INHERITANCE DISTRIBUTION CHILDREN BORN TO MARRIAGES BETWEEN SUNDA WIWITAN FAITH AND ISLAM - Muhammad Rifqi Rafi Drajat; Renny Supriyatni; Bambang Daru Nugroho; Sheila Eldi Azzahra (Cepalo, 2026)
Marriage between Muslims and adherents of the Sunda Wiwitan faith raises legal issues concerning the inheritance rights of children. This study uses empirical legal research based on primary data from interviews and secondary data from legislation, books, journals, and online sources. The research examines inheritance distribution among children born to Muslim fathers and Sunda Wiwitan mothers. The findings show that within the Sunda Wiwitan community, inheritance is distributed equally among children from the father’s estate in the presence of ais pangampih as witnesses. In contrast, Islamic law holds that children born from a marriage not recognized as valid under Islamic law do not have legal lineage to the father in inheritance matters. Current inheritance practices in interfaith marriages therefore conflict with the Receptie in Exit theory in Islamic legal thought, which requires Muslims to follow Islamic legal principles rather than the customary rules of the Sunda Wiwitan belief system. Keywords: Marriage, Inheritance, Islamic Law, Sunda Wiwitan Faith.